A review of biomass burning: Emissions and impacts on air quality, health and climate in China - Chen, J.; Li, C.; Ristovski, Z.; Milic, A.; Gu, Y.; Islam, M.; Wang, S.; Hao, J.; Zhang, H.; He, C.; Guo, H.; Fu, H.; et al. (Elsevier, 2017)
Biomass burning (BB) is a significant air pollution source, with global, regional and local impacts on air quality, public health and climate. Worldwide an extensive range of studies has been conducted on almost all the aspects of BB, including its specific types, on quantification of emissions and on assessing its various impacts. China is one of the countries where the significance of BB has been recognized, and a lot of research efforts devoted to investigate it, however, so far no systematic reviews were conducted to synthesize the information which has been emerging. Therefore the aim of this work was to comprehensively review most of the studies published on this topic in China, including literature concerning field measurements, laboratory studies and the impacts of BB indoors and outdoors in China. In addition, this review provides insights into the role of wildfire and anthropogenic BB on air quality and health globally. Further, we attempted to provide a basis for formulation of policies and regulations by policy makers in China.